2011
DOI: 10.1136/ard.2010.142364
|View full text |Cite
|
Sign up to set email alerts
|

Tissue structure modification in knee osteoarthritis by use of joint distraction: an open 1-year pilot study

Abstract: BackgroundModification of joint tissue damage is challenging in late-stage osteoarthritis (OA). Few options are available for treating end-stage knee OA other than joint replacement.ObjectivesTo examine whether joint distraction can effectively modify knee joint tissue damage and has the potential to delay prosthesis surgery.Methods20 patients (<60 years) with tibiofemoral OA were treated surgically using joint distraction. Distraction (∼5 mm) was applied for 2 months using an external fixation frame. Tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
174
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 23 publications
8
174
0
1
Order By: Relevance
“…In comparison with the earlier open uncontrolled trial [43] the duration of distraction was shortened with two weeks (from eight to six weeks) to limit treatment burden. The rationale for this shortening to six weeks was founded by the fact that biomarker-turnover of cartilage and bone tissue increases within the first four to six weeks of KJD, and thereafter stabilizes as observed in the prospective uncontrolled trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with the earlier open uncontrolled trial [43] the duration of distraction was shortened with two weeks (from eight to six weeks) to limit treatment burden. The rationale for this shortening to six weeks was founded by the fact that biomarker-turnover of cartilage and bone tissue increases within the first four to six weeks of KJD, and thereafter stabilizes as observed in the prospective uncontrolled trial.…”
Section: Methodsmentioning
confidence: 99%
“…With shortening of the distraction period the concern about post-treatment stiffness decreased. In order to further diminish the burden of the patients, a continuous distraction was performed instead of a two weekly interruption for continuous passive motion (CPM) therapy upon temporarily removal of the mono-tubes [43] . In both trials a specified KJD-physiotherapy protocol (based on guidelines for TKP and HTO) was developed to make the whole post-surgical procedure similar for all KJD patients and comparable to HTO and TKP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Studies involving the ankle and knee joints indicated an increase in JSW after treatment similar to manual traction. 16,17,19 However, in these studies, an external fixator was used to apply traction force. Thus, no studies have evaluated the mechanical effect of manual traction of the hip joint on JSW, although this technique is frequently used.…”
mentioning
confidence: 99%
“…This concept that cartilage catabolism in OA may depend upon weight bearing or joint loading is supported by cartilage regeneration occurring following surgical unloading of human joints. 4 Osteoarthritis in humans represents a heterogeneous pathologic process with many potential therapeutic targets. It is therefore unlikely that a single 'magic bullet' will effectively treat all patients.…”
Section: Aetiopathogenesismentioning
confidence: 99%